THE EFFECT OF ENTERPRISE RESOURCE PLANNING IMPLEMENTATION ON INCREASING COMPANY PERFORMANCE - Laulita, Nasar Buntu; Yulfiswandi; Ana; Agustino, Malvin; Rusiana, Nia; Lim, Vera Edelia (Transpublika Publisher, 2022)
The development of the world as a result of current globalization has led to an increase in worldwide competitiveness among businesses. Consequently, businesses always seek performance enhancements that might drive them to the forefront of commercial rivalry. Good supply chain management is one means of enhancing this performance. Enterprise Resource Planning (ERP) is used by many companies. Enterprise Resource Planning (ERP) is a model of an information system that can assist companies in automating and integrating their fundamental business activities. This study aims to examine the impact of ERP on company performance. Using the process of literature review, data and information were acquired from several literature sources. The results reveal that ERP has an effect on a variety of company aspects, including planning, costs, forecasts, and integration. Furthermore, ERP can also influence management performance in terms of supervision, thereby enhancing the efficacy and efficiency of each business line. Additionally, ERP can increase revenue, contributing to enhanced financial performance.